2017
DOI: 10.1016/j.yhbeh.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interpersonal violence-related post-traumatic stress disorder (PTSD) on mother and child diurnal cortisol rhythm and cortisol reactivity to a laboratory stressor involving separation

Abstract: Women who have experienced interpersonal violence (IPV) are at a higher risk to develop posttraumatic stress disorder (PTSD), with dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and impaired social behavior. Previously, we had reported impaired maternal sensitivity and increased difficulty in identifying emotions (i.e. alexithymia) among IPV-PTSD mothers. One of the aims of the present study was to examine maternal IPV-PTSD salivary cortisol levels diurnally and reactive to their child's distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 69 publications
2
45
0
2
Order By: Relevance
“…This result is consistent with cross-species research in both rodents and nonhuman primates showing that the caregiver buffers offspring stress response by regulating HPA axis activity (Moriceau & Sullivan, 2006;Sanchez et al, 2015). That is, around 24 months, the infant may have sufficiently developed social cognitive skills and be better able to interpret subtle and indirect cues from the caregiver, thus facilitating social buffering (Feldman, 2007;Frith, 2008;Hostinar et al, 2014;Tomasello et al, 2005 & Gunnar, 2016;Cordero et al, 2017), and in particular among low-income children (Raffington et al, 2018). The fact that we found a potential maternal buffering effect at 24 months, but not at 7 or 15, possibly indicates a developmental effect.…”
Section: Associations Between Mother and Infant Cortisol At 24 Monthssupporting
confidence: 86%
See 1 more Smart Citation
“…This result is consistent with cross-species research in both rodents and nonhuman primates showing that the caregiver buffers offspring stress response by regulating HPA axis activity (Moriceau & Sullivan, 2006;Sanchez et al, 2015). That is, around 24 months, the infant may have sufficiently developed social cognitive skills and be better able to interpret subtle and indirect cues from the caregiver, thus facilitating social buffering (Feldman, 2007;Frith, 2008;Hostinar et al, 2014;Tomasello et al, 2005 & Gunnar, 2016;Cordero et al, 2017), and in particular among low-income children (Raffington et al, 2018). The fact that we found a potential maternal buffering effect at 24 months, but not at 7 or 15, possibly indicates a developmental effect.…”
Section: Associations Between Mother and Infant Cortisol At 24 Monthssupporting
confidence: 86%
“…In turn, because socioeconomic risk was associated with higher maternal cortisol levels, it may be the case that socioeconomic risk was indirectly affecting infant cortisol activity through the caregiver's stress physiology. Several studies have found flat or blunted cortisol responses in infants and toddlers who experienced early life stress (e.g., Sturge-Apple et al, 2012;Koss, Mliner, Donzella, & Gunnar, 2016;Cordero et al, 2017), and in particular among low-income children (Raffington et al, 2018). Importantly, flat or blunted cortisol responses to stressors may be an adaptive response in the short term; however, they may negatively impact later cognitive, behavioral, and physical health outcomes (Blair, Granger, & Razza, 2005;Ginty, Phillips, Roseboom, Carroll, & Derooij, 2012;Taylor, 2010).…”
Section: Associations Between Mother and Infant Cortisol At 24 Monthsmentioning
confidence: 99%
“…Lower cortisol and blunted cortisol reactivity were present in preadolescent boys and girls with maternal PTSD, even after controlling for youth traumatic event history and mental health symptoms. A blunted cortisol reactivity to stress was observed in even younger offspring, toddlers aged 12‐48 months, in association with maternal PTSD occurring as a result of interpersonal violence. Infants of women exposed to maternal child abuse also displayed lower baseline cortisol when examined at 6 months of age.…”
Section: The Introduction Of Biological Research Into the Study Of Inmentioning
confidence: 93%
“…For example a recent study of hair cortisol, which provides a window into overall adrenocortical arousal across the past weeks or months, revealed a positive association between mothers' report of injury events and child cortisol (Boeckel, Viola, Daruy-Filho, Martinez, & Grassi-Oliveira, 2017). To date, only one study has examined child diurnal cortisol rhythms in relation to IPV (Cordero et al, 2017). Cordero and colleagues found no association between IPV exposure and diurnal cortisol across the day, however, cortisol was only collected on one day and the sample contained only 12 IPV exposed and 8 control toddlers (Cordero et al, 2017).…”
mentioning
confidence: 99%
“…In particular, research has consistently documented a link between mothers' experience of IPV and lower levels of warm, supportive, and positive parenting (Chiesa et al, 2018;Gustafsson et al, 2012;Levendosky & Graham-Bermann, 2000); whereas research on the extent to which IPV relates to autonomy supportive versus harsh and controlling parenting is less clear (Chiesa et al, 2018;Levendosky & Graham-Bermann, 2000). Physiologically, IPV has been found to flatten mothers' cortisol diurnal rhythms (Kim et al, 2015;Saxbe et al, 2015) due to heightened evening/ bedtime levels of cortisol (Kim et al, 2015;Pico-Alfonso, Garcia-Linares, Celda-Navarro, Herbert, & Martinez, 2004), or reduced waking cortisol when paired with posttraumatic stress disorder (Cordero et al, 2017). However, few studies have examined the potential for IPV to indirectly impact child diurnal cortisol regulation through dysregulations in maternal behavior and physiology.…”
mentioning
confidence: 99%